Hubungan Tradisi Munjung dengan Sikap Keagamaan Masyarakat Desa Panjalin Lor Kecamatan Sumberjaya Kabupaten Majalengka - Somantri Somantri (Misykah : Jurnal Pemikiran dan Studi Islam, 2020)
The relationship between Munjung's radiation and religious attitudes fosters the strengthening of local character and traditions of the community. The aspect studied is the existence of Munjung as a strengthening of local character and traditions in Panjalin Lor Village, Sumberjaya District, Majalengka Regency. Qualitative research is chosen as a method for exploring and understanding meanings ascribed to social or humanitarian problems, focusing on individual meanings, and translating the complexity of a problem. Descriptive data is developed from the results of obtaining a number of written and oral information from observations. Munjung as a tradition and culture for the residents of Panjalin Lor becomes the spirit of a religious attitude by not seeing that Munjung is a form of denial of religious practice (Islam) which will still be done because as a form of cultural ngarumat, maintaining a good tradition to remember the struggles of the old grandmothers. serve the community as well as maintain and maintain togetherness among the villagers of Panjalin Lor as Sundanese who are influenced by the fighting motto of the Sundanese people, namely; "Choose Asih Choose Asah and Choose Foster.". Abstrak Hubungan radisi Munjung dengan Sikap Keagamaan menumbuhkan Penguatan Karakter dan Tradisi Lokal Masyarakat. Aspek yang dikaji adalah Eksistensi Munjung sebagai Penguatan Karakter dan Tradisi Lokal di Desa Panjalin Lor Kecamatan Sumberjaya Kabupaten Majalengka. Penelitian kualitatif dipilih sebagai metode untuk mengekplorasi dan memahami makna yang dianggap berasal dari masalah sosial atau kemanusian, berfokus pada makna individual, dan menerjemahkan komplesitas suatu persoalan. Data deskriptif dikembangkan dari hasil perolehan sejumlah informasi tertulis maupun lisan dari hasil pengamatan. Munjung sebagai tradisi dan budaya bagi warga Panjalin Lor menjadi spirit dari sikap keagamaan dengan tidak memandang bahwa munjung adalah sebagai bentuk pengingkaran pada praktik keagamaan (Islam) yang akan tetap dilakukan karena sebagai bentuk ngarumat budaya, memelihara tradisi yang baik guna mengingat perjuangan para Buyut yang sudah berjasa terhadap masyarakat sekaligus memelihara dan menjaga kebersamaan antarwarga desa Panjalin Lor sebagai orang Sunda yang dipengaruhi oleh moto juang hidup orang Sunda yaitu; “Silih Asih Silih Asah dan Silih Asuh.”.